Gamma Ray Irradiation On Several Rice VarietiesAt The Seed Germination Phase - Siti Hartati Yusida Saragih; Kamsia Dorliana Sitanggang; Nazra Melisa Munthe (International Journal of Science and Environment (IJSE), 2025)
Rice (Oryza sativa L.) is a strategic food commodity and a primary source of carbohydrates for most of the world's population, including Indonesia. One effort to increase rice production is through mutation.The purpose of this study is to study the influencegamma ray irradiation on several rice varieties at the germination seedling phase. Gamma ray irradiation was carried out in January 2025 at the Center for Isotope and Radiation Applications (PAIR), National Nuclear Energy Agency (BATAN), Pasar Jumat, Jakarta, while planting was carried out on Jl. Belibis, Rantau Selatan District, Labuhanbatu Regency in March 2025. The study used a non-factorial Completely Randomized Design (CRD) namely gamma ray irradiation at the following doses: 0 Gy (control/no radiation dose); 50 Gy; 100 Gy; 150 Gy; 200 Gy; 250 Gy; 300 Gy; 350 Gy; 400 Gy and 450 Gy.Observations were made on germination rate, seedling height, and root length. The data were analyzed using analysis of variance followed by Duncan's multiple range test (DMRT). The results showed a visible effect of gamma ray irradiation on germination rate. Gamma ray irradiation also affected average seedling height and root length.The lowest reduction in germination and seedling height occurred in the Sibenang rice variety at a dose of 450 Gy, at 0%. Meanwhile, the shortest root length was in the Ciherang rice variety at a dose of 450 Gy, at 1.93 cm.